A Genetic Structuralism Analysis of Materialism in Frances Hodgson Burnett’s A Little Princess - Nurul Berlian Aisyah Sakinah; Dina Dyah Kusumayanti (POETIKA, 2023)
Although the Industrial Revolution in Britain’s Victorian era contributed significantly toward Britain’s development, it also led to the emergence of materialism issues in society. This research aims to identify how materialism was constructed and to reveal the worldview on materialism expressed in A Little Princess (2017). Goldmann’s Genetic Structuralism is operated in this qualitative research. The results indicate that the materialism issue brought some adverse impacts or social problems, such as the division of social classes, the social gap between the upper, middle, and working classes, and child labor in the Victorian age. Besides, the worldview of Burnett’s social group resisted materialism by delineating these social issues and a binary opposition between a materialistic character shown by Miss Minchin and a non-materialistic character presented by Sara. Through the binary opposition, Burnett wanted readers to be aware of the negative impacts of practicing materialistic traits such as possessiveness, envy, and non-generosity. Possessiveness is shown by Miss Minchin's desire and attitude to retain all of Sara’s luxury stuff. Envy appears in Miss Minchin's envy of Sara’s wealth and prosperity. Non-generosity as Miss Minchin hard to donate her possessions or do charity. As a human fact product, A Little Princess can be interpreted as a view to getting a better life for poor child workers at that time.